The Potential of Carbon Sequestration in the Sanctuary Maleo Hungayono Resort TulaboloPinogu Nani Wartabone Bogani National Park Area - Hamid, Ririn Septiani; K Baderan, Dewi Wahyuni; Hamidun, Marini Susanti; Katili, Abubakar Sidik (Indonesian Journal of Chemistry and Environment, 2024)
A forest is a unified ecosystem in the form of an expanse of land containing biological natural resources. It is dominated by trees in one natural environment and another so that they cannot be separated. Forests play an important role in maintaining the balance of carbon dioxide in the atmosphere. Their plants can absorb carbon dioxide from the air during the photosynthesis process so they play an important role in maintaining climate balance. The Maleo Hungayono Sanctuary is a place for endemic animals including forests in the Bogani Nani Wartabone National Park area which cannot produce wood, so what will be the strength of the economic value of the TNBNW area is environmental services, including carbon. This research aims to determine the potential for carbon uptake in the Maleo Hungayono Sanctuary, Bogani Nani Wartabone National Park Area. The research results show that the highest biomass value at the research location is at the tree level with a total carbon uptake of 16,588.26 tons/ha; at pole level with total carbon uptake of 722.65 tonnes/ha; at the sapling level with a total carbon uptake of 63.91 tonnes/ha.